HAK PILIH (KHIYAR) DALAM TRANSAKSI JUAL BELI DI MEDIA SOSIAL MENURUT PERSPEKTIF HUKUM ISLAM - Subhan ZA., Moh. Ah. (Universitas Islam Lamongan, 2017)
Islam has taken into account the right to select (khiyar) in buying and selling transaction with the aim of avoiding possible fraud, forgery and so on so as to create a willingness between each party. Khiyar could be conducted when sellers and buyers meet directly physically as that in any buying and selling transaction. While in the modern buying and selling process done in cyberspace, especially in social media such transaction raises the question